If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = (y + 6u)(7y + -7u + -5) Reorder the terms: 0 = (6u + y)(7y + -7u + -5) Reorder the terms: 0 = (6u + y)(-5 + -7u + 7y) Multiply (6u + y) * (-5 + -7u + 7y) 0 = (6u * (-5 + -7u + 7y) + y(-5 + -7u + 7y)) 0 = ((-5 * 6u + -7u * 6u + 7y * 6u) + y(-5 + -7u + 7y)) Reorder the terms: 0 = ((-30u + 42uy + -42u2) + y(-5 + -7u + 7y)) 0 = ((-30u + 42uy + -42u2) + y(-5 + -7u + 7y)) 0 = (-30u + 42uy + -42u2 + (-5 * y + -7u * y + 7y * y)) Reorder the terms: 0 = (-30u + 42uy + -42u2 + (-7uy + -5y + 7y2)) 0 = (-30u + 42uy + -42u2 + (-7uy + -5y + 7y2)) Reorder the terms: 0 = (-30u + 42uy + -7uy + -42u2 + -5y + 7y2) Combine like terms: 42uy + -7uy = 35uy 0 = (-30u + 35uy + -42u2 + -5y + 7y2) Solving 0 = -30u + 35uy + -42u2 + -5y + 7y2 Solving for variable 'u'. Remove the zero: 30u + -35uy + 42u2 + 5y + -7y2 = -30u + 35uy + -42u2 + -5y + 7y2 + 30u + -35uy + 42u2 + 5y + -7y2 Reorder the terms: 30u + -35uy + 42u2 + 5y + -7y2 = -30u + 30u + 35uy + -35uy + -42u2 + 42u2 + -5y + 5y + 7y2 + -7y2 Combine like terms: -30u + 30u = 0 30u + -35uy + 42u2 + 5y + -7y2 = 0 + 35uy + -35uy + -42u2 + 42u2 + -5y + 5y + 7y2 + -7y2 30u + -35uy + 42u2 + 5y + -7y2 = 35uy + -35uy + -42u2 + 42u2 + -5y + 5y + 7y2 + -7y2 Combine like terms: 35uy + -35uy = 0 30u + -35uy + 42u2 + 5y + -7y2 = 0 + -42u2 + 42u2 + -5y + 5y + 7y2 + -7y2 30u + -35uy + 42u2 + 5y + -7y2 = -42u2 + 42u2 + -5y + 5y + 7y2 + -7y2 Combine like terms: -42u2 + 42u2 = 0 30u + -35uy + 42u2 + 5y + -7y2 = 0 + -5y + 5y + 7y2 + -7y2 30u + -35uy + 42u2 + 5y + -7y2 = -5y + 5y + 7y2 + -7y2 Combine like terms: -5y + 5y = 0 30u + -35uy + 42u2 + 5y + -7y2 = 0 + 7y2 + -7y2 30u + -35uy + 42u2 + 5y + -7y2 = 7y2 + -7y2 Combine like terms: 7y2 + -7y2 = 0 30u + -35uy + 42u2 + 5y + -7y2 = 0 The solution to this equation could not be determined.
| -12x-20=-10x-15 | | -2x-10=3x-15 | | fn=5n+6 | | 16x-10+9=99-30x | | 6cosx+5=-5cosx+14 | | x+.05x=252000 | | (6x-5)(8x+3)=0 | | 187=-x+8 | | x+.05x=456 | | x+.05x=110 | | f(x)=x^3-6x^2-x+6 | | p^6-1=0 | | Y=-14x*-70x | | 2x/11 | | 3x+6x+2=-4x | | 10+10x=50+2x | | 8+w-4.7w-.5= | | 15x^2+26x+7= | | 125x^6-8=equation | | -4/9x=8 | | 5/√5xy^2 | | 5/√(5xy^2 | | 0=x^2+x-8 | | 80p^2r-245b^2r=0 | | 2v^2-10+12=0 | | 16v^4y^5-4v/4v^3x^6 | | 2r=7(r-15) | | 6m+3(2m-1)=-27 | | 5lnx-4=7 | | -9+20x=16 | | 5=-10n | | r=7r-52.5 |